My little pony : the man in the moon and the treasure hunt (Manchester : Cliveden Press, 1986)
A short story featuring the ponies, including Twilight, Majesty, Moondancer, Medley, Applejack and more, as well as a couple of puzzles and games.
Keywords: Children's stories; Animal fiction